Penentuan Klasifikasi Tanah Dengan Menggunakan Metode Multi-channel Analysis of Surface Waves Di Kapanewon Pleret, Kabupaten Bantul - Zawawi, Aditya Fais; Sunardi, Bambang; Setyoajie Prayoedhie, Setyoajie (Stasiun Geofisika Kelas I Sleman, 2023)
Kapanewon Pleret, Bantul Regency, is one of the areas prone to earthquakes. One of the earthquakes that occurred was the 27 May 2006 earthquake with a magnitude of 6.3. The area most heavily affected by the earthquake was Kapanewon Pleret. The average shear wave velocity to a depth of 30 m (Vs30) is an important criterion in determining soil type classification. One geophysical method for determining Vs30 is the Multichannel Analysis of Surface Wave (MASW) method. The results of research in Kapanewon Pleret using the MASW method show that the Vs30 value in Kapanewon Pleret, Bantul Regency, is in the range of 212 – 396 m/s. Based on the Vs30 value that has been obtained, it can be classified that the soil types in Kapanewon Pleret, Bantul Regency, are dominated by medium soil (SD), and a small portion of very dense soil (SC).